Impact of bilingual education on student achievement - Aimee Chin (IZA World of Labor, 2015)
More than 4.4 million students enrolled in US public schools participate in English language learner programs because of linguistic barriers to learning in regular classrooms. Whether native language instruction should be used in these programs is a contentious issue. Recent studies, using credible research designs for estimating causal impacts, find that bilingual education programs (which use some native language instruction) and English-only programs are not significantly different in their impact on standardized test performance. This finding suggests that it is time to change the focus from use of the native language to program quality.
Keywords: I21; J24; 330; bilingual education; language of instruction; English as a second language; structured English immersion; limited English proficient students; English language learners